Assessment of obstructive sleep apnea among malaysian with open-angle glaucoma using the STOP-BANG questionnaire - Sivaratnam, Dhashani; Yusof Khan, Abdul Hanif Khan; Devaraj, Navin Kumar; Subha, Sethu Thakachy; Muteb, Obed Twesan; Mohamad Zain, Muhsonat; Abdul Rahim, Nur Syazwani; Abu Bakar, Saraiza; Lakshman, Anand Jebaraj; Ew, Shao Chen; Kanasan, Kirbashini; Baharuddin, Nur Najlaa; et al. (University of Malta, 2024)
Introduction: Glaucoma is the most common cause of irreversible loss of vision worldwide. Numerous studies have confirmed an association between open-angle glaucoma (OAG) and obstructive sleep apnea (OSA) among Caucasian and Chinese populations; however, there has been no published study from South East Asia on this subject. Materials and Methods: Therefore, our objectives were to use the STOP-BANG questionnaire (SBQ) to determine the factors (socio-demography, medical comorbidities) associated with the risk of OSA among patients with OAG and the association between glaucoma parameters and OSA. The SBQ was used for classifying patients as OSA low risk (score ≤ 2) to moderate/high risk (score ≥ 3). Results: We found that the mean patient age was 64.2 ± 8.9 years, of which 55.4% (245 subjects) were males. The prevalence of moderate/high risk of OSA among the open angle glaucoma patients was 247 (55.9%), which comprised of mostly males(n=196,44.34%) compared to females (n=51,11.54%). Multiple logistic regression analysis showed that the predictors of moderate/high risk of OSA were males [odds ratio (OR) = 189.7, 95% confidence interval (CI) = 55.21, 651.69], high body mass index (OR = 1.23, 95% CI = 1.14, 1.33), diabetes (OR = 3.1, 95% CI = 1.45, 6.63) and hypertension (OR = 70.73, 95% CI = 22.59,221.50). Conclusion: The identification of modifiable risk factors will be beneficial in the prevention of visual loss from glaucoma. The prevalence of moderate to high risk OSA risk was 56.9% among patients with OAG, that supports the vascular theory causing glaucomatous damage.